Ekonomi Kreatif, Upaya Meningkatkan Ekonomi Masyarakat Desa dan Mengurangi Dampak Limbah Plastik - Dadang Amiruddin (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
The aim of Kuliah Kerja Mahasiswa (KKM) Banten Jaya University (Unbaja) 2019 are improves the skills and creativity of the society of Cikolelet, specifically for women / housewives. The problem that is being face at the moment is that people don't understand how to utilizing used plastic drink waste that can have economic value. The method of implementing this program is (1) field monitoring, interviews, and exploring potentials, (2) providing handicraft training from waste materials used in plastic beverage glass lid (3) providing knowledge on how to do online marketing of handicraft products. The result of this program is that the society of Cikolelet have the skills and creativity in managing plastic waste that can have economic value. With this program it is hoped that the society of Cikolelet can improve their creativity so that they can support Cikolelet as a Tourism Village.